A Comparative Study of Central Corneal Epithelial, Stromal, and Total Thickness in Males With and Without Primary Open-Angle Glaucoma. Issue 6 (June 2018) - Batawi, Hatim; Lollett, Ivonne Valentina; Maliakal, Cima; Wellik, Sarah R.; Anderson, Michael G.; Feuer, William; Karp, Carol L.; Galor, Anat
Abstract : Purpose: To compare the central corneal epithelial thickness (CET), stromal thickness (CST), and total thickness (CCT) in males with and without primary open-angle glaucoma and to determine the factors associated with corneal thickness. Methods: A case–control study was conducted to evaluate 116 male patients at the Miami Veterans Affair Medical Center. Subjects with available anterior segment optical coherence tomography images (Cirrus HD-OCT, Carl Zeiss Meditec Inc, Dublin, CA) were retrospectively classified into 2 groups by glaucoma status. CET, CST, and CCT measurements between the groups were compared. Associations between thickness and other variables of interest were also evaluated. Results: The 2 groups were similar with respect to race and ethnicity. Mean age of patients in the glaucoma group (70.3 ± 8.9) was higher than in the nonglaucoma group (66.0 ± 11.7), P < 0.03. Individuals who self-identified as black had lower CST (447.8 ± 29.0 μm) and CCT (503.0 ± 30.5 μm) compared with whites (CST: 470.0 ± 31.7 μm; CCT: 525.1 ± 32.4 μm), P = 0.0001 and P = 0.0002, respectively. In a similar manner, individuals with glaucoma had lower CST (453.4 ± 32.5 μm) and CCT (507.3 ± 33.8 μm) than that of those without glaucoma (CST: 465.2 ± 31.2 μm; CCT: 521.5 ± 31.5 μm), P = 0.05 and P = 0.02, respectively. CET, CST, and CCT were negatively correlated with the number of antiglaucoma medications (r = −0.2, r = −0.22, and r = −0.25, respectively), P = 0.05 for all. Conclusions: Individuals with glaucoma have lower CST and CCT measurements compared with individuals without glaucoma. An increased number of glaucoma medications were associated with lower thickness measurements.